2013
DOI: 10.1371/journal.pone.0080343
|View full text |Cite
|
Sign up to set email alerts
|

Injections, Cocktails and Diviners: Therapeutic Flexibility in the Context of Malaria Elimination and Drug Resistance in Northeast Cambodia

Abstract: BackgroundAdherence to effective malaria medication is extremely important in the context of Cambodia’s elimination targets and drug resistance containment. Although the public sector health facilities are accessible to the local ethnic minorities of Ratanakiri province (Northeast Cambodia), their illness itineraries often lead them to private pharmacies selling “cocktails” and artemether injections, or to local diviners prescribing animal sacrifices to appease the spirits.MethodsThe research design consisted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(82 citation statements)
references
References 19 publications
5
77
0
Order By: Relevance
“…For example, a large-scale survey in endemic areas of northeast India revealed that 39.2% of adults living in a household which had contained a malaria sufferer in the previous three months visited a TH ( Vaidya ) [ 35 ]. Another study in northeast Cambodia found 14.4, 37.3 and 40.1% people used herbal treatment, animal sacrifice and coin massage, respectively, to treat malaria [ 36 ]. Regardless of the variability in TM and TH user rates across the different studies reviewed, the empirical literature does appear to demonstrate substantial prevalence rates for TM/TH use among malaria patients or people in malaria-endemic areas across a number of Asia-Pacific countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, a large-scale survey in endemic areas of northeast India revealed that 39.2% of adults living in a household which had contained a malaria sufferer in the previous three months visited a TH ( Vaidya ) [ 35 ]. Another study in northeast Cambodia found 14.4, 37.3 and 40.1% people used herbal treatment, animal sacrifice and coin massage, respectively, to treat malaria [ 36 ]. Regardless of the variability in TM and TH user rates across the different studies reviewed, the empirical literature does appear to demonstrate substantial prevalence rates for TM/TH use among malaria patients or people in malaria-endemic areas across a number of Asia-Pacific countries.…”
Section: Resultsmentioning
confidence: 99%
“…A Malaysian study reported the use of medicinal plants for curative purposes regarding malaria through their application via bathing or compressing the enlarged spleen during traditional rituals [ 44 ], and an Indian qualitative study reported herb use and application [ 57 ]. There is evidence of other traditional ways with which Asian Pacific populations attempt to treat or prevent malaria, such as using faith healing [ 38 , 50 , 56 ], coin massage [ 36 ] and massage [ 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When private and public sectors overlap, and genuine and fake diagnostics and treatments are often indistinguishable, patients build their decisions on trust in particular providers and on lay empiricism based on observations of patient improvement after treatment (Gryseels et al, 2013). This system prevails as long as both client and provider maintain their bargaining power (Van Staa & Hardon, 1996).…”
Section: Discussionmentioning
confidence: 99%